1999
DOI: 10.1111/j.1600-0773.1999.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Toremifene on Bone and Uterine Histology and on Bone Resorption in Ovariectomised Rats

Abstract: The effect of the selective oestrogen receptor modulator, toremifene, to inhibit ovariectomy-induced bone loss was studied in rats. The oral doses were 0.3, 3.0 or 30 mg/kg/day for 2 months. 17P-oestradiol ( 5 pgikgiday, subcutaneously) was used as positive control. One group was also treated with a combination of 17P-oestradiol (5 pgikg) and toremifene (3.0 mgikg). Biochemical markers were urinary hydroxyproline and calcium (adjusted with urinary creatinine levels) and the serum level of pyridinoline cross-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…As monotherapy TOR has a significant and equivalent stimulatory effect on uterine epithelium as TAM. These monotherapy findings are consistent with published studies in this rat model [24][25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 94%
“…As monotherapy TOR has a significant and equivalent stimulatory effect on uterine epithelium as TAM. These monotherapy findings are consistent with published studies in this rat model [24][25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 94%
“…Our results confirmed that TOR has positive and beneficial effects on bone and lipid metabolism in as far as TOR significantly increased BMD, as well as significantly reduced the rise in serum cholesterol, LDL and TG induced by OVX. However, TOR had a significant stimulatory effect on uterine epithelium [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 95%